1983
DOI: 10.1111/j.1365-2362.1983.tb00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Na+K+ cotransport function in a group of patients with essential hypertension

Abstract: In 50 normotensive controls, the increase in erythrocyte Na+ concentration up to 12.4 k 2.0 mmol/l cells (mean & SD) ensures half-maximal stimulation of outward Na+,K+ cotransport fluxes. Fortysix out of sixty-five patients with essential hypertension required more than 16 mmol/l cells of internal Na+ concentration to obtain a similar effect, strongly suggesting an abnormal cotransport function.Seven out of fourteen hypertensive patients with normal Na,K cotransport function showed Na+ ,Li+ countertransport fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
2

Year Published

1986
1986
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 30 publications
3
39
2
Order By: Relevance
“…Ferret red cells thus provide an excellent system in which to examine factors which might control the activity of the co-transport system. Recent theories assign key roles to the cotransport system in the activation of secretion in epithelia (Petersen & Maruyama, 1984) and in the genesis of some types of essential hypertension (see, for instance, Garay, Dagher, Pernollet, Devynck & Meyer, 1980;Garay, Nazaret, Hannaert & Price, 1983). Alterations in intracellular ionized calcium concentration are central to these theories (see also Blaustein, Lang & James-Kracke, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Ferret red cells thus provide an excellent system in which to examine factors which might control the activity of the co-transport system. Recent theories assign key roles to the cotransport system in the activation of secretion in epithelia (Petersen & Maruyama, 1984) and in the genesis of some types of essential hypertension (see, for instance, Garay, Dagher, Pernollet, Devynck & Meyer, 1980;Garay, Nazaret, Hannaert & Price, 1983). Alterations in intracellular ionized calcium concentration are central to these theories (see also Blaustein, Lang & James-Kracke, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding ion transport in erythrocytes, the total population of patients with essential hypertension is heterogeneous and includes a subgroup of higher Na + -Li + CT flux with normal Na + -K + cotransport (COT) function and one of abnormal Na + -K + COT function with normal Na + -Li + CT flux (36). In hypertensive patients, Na…”
Section: Ion Exchangersmentioning
confidence: 99%
“…These observations subsequent-ly were confirmed in some laboratories, 13 but other investigators 14 " 17 using different methodology found normal inward cotransport or increased values of outward cotransport in RBCs from their hypertensive populations. Garay and co-workers 18 ' l9 later extended their original observations to examine the kinetics of RBC Na + -K + cotransport in hypertensive patients by Na; activation of Na and K efflux in RBCs loaded at several concentrations of Na,. A substantial portion of their hypertensive study population had decreased apparent affinity (increased K 05 ) for internal Na in activating outward Na + -K + cotransport.…”
mentioning
confidence: 99%